1998
DOI: 10.1128/jb.180.21.5799-5802.1998
|View full text |Cite
|
Sign up to set email alerts
|

CHR, a Novel Family of Prokaryotic Proton Motive Force-Driven Transporters Probably Containing Chromate/Sulfate Antiporters

Abstract: We describe a small family of proteins, CHR, which contains members that function in chromate and/or sulfate transport. CHR proteins occur in bacteria and archaea. They consist of about 400 amino acyl residues, appear to have 10 transmembrane α-helical segments in an unusual 4+6 arrangement, and arose by an intragenic duplication event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 31 publications
1
58
1
1
Order By: Relevance
“…Although bootstrap supporting values were relatively low, all resulting trees were similar, regardless of the algorithms employed to perform the phylogenetic analysis. This pattern suggests that bulk LCHR proteins conform to a monophyletic group, and agrees with the proposal that the origin of bidomain LCHR proteins was an ancient duplication followed by a gene fusion of two ancestral monodomain CHRs [3,8].…”
Section: ): (A)supporting
confidence: 89%
See 1 more Smart Citation
“…Although bootstrap supporting values were relatively low, all resulting trees were similar, regardless of the algorithms employed to perform the phylogenetic analysis. This pattern suggests that bulk LCHR proteins conform to a monophyletic group, and agrees with the proposal that the origin of bidomain LCHR proteins was an ancient duplication followed by a gene fusion of two ancestral monodomain CHRs [3,8].…”
Section: ): (A)supporting
confidence: 89%
“…The C. metallidurans ChrA protein (from the LCHR2 subfamily) has been reported to have 10 TMSs, with the amino and carboxyl terminal domains similarly oriented with respect to the membrane axis [8]. By contrast, the P. aeruginosa ChrA protein (from the LCHR5 subfamily) was found to possess a 13 TMS arrangement, with the amino and carboxyl terminal domains oppositely oriented [13].…”
Section: Membrane Topology Of Schr Proteinsmentioning
confidence: 99%
“…With these data, the topology of the first half of P. aeruginosa ChrA, composed of six TMS, was shown to be different from that reported for the amino terminus of its C. metallidurans homolog, with only four TMS in this protein half. Comparison of reporter enzyme activities between fusions from the two ChrA proteins shows that Phe69 from Pseudomonas ChrA yielded a high PhoA value (Aguilera et al, 2004), whereas Thr60 in the Cupriavidus protein showed high LacZ (Nies et al, 1998). These data confirm a different topology for the first 70 amino acids at the N-terminal part of the two transporters.…”
Section: Discussionmentioning
confidence: 65%
“…Fourteen-TMS proteins from the MFS contain two extra TMS in the middle of the two 6-TMS primordial domains (Paulsen et al, 1996;Pao et al, 1998). Opposite examples have been reported for the already mentioned ChrA homolog from C. metallidurans (Nies et al, 1998) and for members of the OLF (oligosaccharidyl-lipid flippase) family (Hrovup et al, 2003). These proteins seem to have evolved from 12-TMS to 10-TMS polypeptides by the substitution of hydrophobic amino acids with hydrophilic residues (Nies et al, 1998;Hrovup et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…A ChrA homolog, also conferring chromate resistance, was found in an Alcaligenes eutrophus plasmid [2]. Several putative homologs have also been found in bacterial complete genome sequences [3,4]. Chromate tolerance conferred by the ChrA protein was associated to diminished accumulation of 51 CrO 23 4 [1,2].…”
Section: Introductionmentioning
confidence: 99%